Investigation of Spatial Change of Air Quality of Southeast Anatolia Region Provinces Using GIS (2007-2019) - Ercan Vural (Doğal Afetler ve Çevre Dergisi)
With the industrial revolution, environmental problems have diversified and have increased significantly, affecting both the natural and the human environment. Air pollution, which is among the most important of these environmental problems, has been a serious problem today as it was in the past. In this study, which examines the human factors affecting air quality and pollution between 2007-2019 in the provinces of Southeast Anatolia Region, pollution shows continuity especially in certain provinces. Depending on this continuity, our aim is to detect air pollution in the provinces of the region and offer solutions to them. IDW (Inverse Distance Weighting) analysis was used through Geographic Information Systems to detect the spatial change of air pollution. With this analysis method, interpolation was provided between the measurements. The provinces with the highest SO2 concentration are Şanlıurfa and Siirt in 2007, Şırnak in 2012, Şanlıurfa and Siirt in 2017 and Şanlıurfa in 2019. PM10 annual average concentration is high in Batman in 2007, Gaziantep, Batman and Siirt in 2012, Şanlıurfa in 2017 and Şırnak in 2019. The number of population living in the city, the type and quality of fuel used in residences and industry, the number of industrial enterprises and the number of vehicles are among the important human factors affecting pollution. In this sense, local and national administrations should take serious measures in the air pollution that causes human health to deteriorate or even die.